Pelatihan Dasar Fotografi Dan Desain Grafis Sebagai Penunjang Optimalisasi Digital Marketing Desa Wisata Belik Depok (Desa Nglewan) - Ahmad Ahsan Ansori; Ahmad Kirom (Journal of Communication Studies, 2023)
The belik depok tourist is one of the first tourists in the village of nglewan, samet district district of ponorogo. The tourism was established by the surrounding communities following the host of a tourist village program with a view to preserving local cultures and also to introducing the potential in the village of nglewan. The digital age could be a big move to make the tourism known and enjoyed by visitors, but because of the lack of human resources that have the expertise in digital marketing, which has resulted in the loss of travel to both local and non-local. In this activity the writer uses a method of completion of literature in harmony with the problem, among which are pretests on the preparation and debriefing to be used, the discussion and practice and managing of the photo results. The objective of this training is to contribute to the marketing of the digital age in order to attract the interest of visiting both local and manca countries